Marie-Laure Ryan e Jan-Noël Thon, Storyworlds across Media. Toward a Media-Conscious Narratology (ENTHYMEMA, 2014)
Recensiamo Marie-Laure Ryan e Jan-Noël Thon eds, Storyworlds across Media. Toward a Media-Conscious Narratology